Clinical, magnetic resonance imaging, and histological description of a choroid plexus papilloma with disseminated intraventricular and spinal cerebrospinal fluid drop metastases in a young adult dog: a case report - Albertini, Guillaume Marc; Malbon, Alexandra; Staudacher, Anne; Stabile, Fabio (Frontiers in Veterinary Science, 2023)
A 2-year-old male entire Cane Corso was presented for investigations into a 1-week history of ambulatory paraparesis and pelvic limbs ataxia gradually deteriorating. Magnetic resonance imaging (MRI) revealed intraventricular space-occupying lesions affecting the fourth ventricle and lateral apertures and intradural-extramedullary space-occupying lesions at the level of C7 vertebra, L4-L5 and L7-S1 intervertebral disc spaces. Due to poor quality-of-life, the patient was euthanised. Post-mortem examination revealed partially encapsulated, multifocally infiltrative, moderately cellular neoplastic masses. The histological description was similar for all masses. The cells appeared cuboidal with round central nuclei and a moderate amount of eosinophilic cytoplasm and were arranged almost exclusively in single layered papilliform patterns supported by fibrovascular stroma. Mitoses were rarely observed (1/2.37 mm 2 ). The primary neoplasm was morphologically most consistent with a choroid plexus papilloma despite drop metastases. This is the first report of a histologically confirmed primary ventricular choroid plexus papilloma causing disseminated MRI-apparent intraventricular and spinal drop metastases.